Effect on system productivity through inter crop diversification in agri-horti system in arid ecosystem of western Rajasthan (Indian Journal of Arid Horticulture, 2020)
An experiment was conducted on the "study of system productivity through intercrop diversification in agri-horti system in arid ecosystem of western Rajasthan" at research farm of ICAR-CAZRI, Regional Research Station, Bikaner on the existing plantation of 10 year old plantation of citrus (Citrus aurentifolia), bael (Aegle marmelose) and gonda (Cordia myxa) planted with drip irrigation system under agri-horti system. The experiment was conducted under factorial Randomized Block design with three replications. The experimental results revealed that the intercropping of legumes (rainfed) has no competition in agri-horti system, showing positive effect on growth and yield of fruit trees. Growth parameters of all the trees were found to be non- significant in intercropping of Lasiurus sindicus and aloe-vera over no intercropping. Intercropping of mothbean with bael gave highest plant height of bael which was 15.9, 13.05, 4.90 and 10.70 per cent higher over intercropping of clusterbean, aloe-vera, L. scindicus and sole, respectively. Yield of intercrops were highest with citrus and lowest with bael during both the years. Highest water use efficiency (0.98 kg/mm) was in intercropping of mothbean with citrus whereas in perennial crops, L. sindicus showed highest WUE of 19.4 kg/mm in intercropping with citrus. The CEY was highest in all the crops in intercropping with citrus over rest of the trees under agri-horti system.
Keywords: Agri-horti system; arid ecosystem; clusterbean equivalent yield; water use efficiency